2021
DOI: 10.1111/hepr.13630
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis improvement assessed by magnetic resonance elastography and Mac‐2‐binding protein glycosylation isomer in patients with hepatitis C virus infection receiving direct‐acting antivirals

Abstract: Aim Fibrosis regression has been observed in patients with chronic hepatitis C virus (HCV) infection treated with direct‐acting antivirals. This study was aimed at evaluating dynamic changes of serum Mac‐2‐binding protein glycosylation isomer (M2BPGi) in patients with HCV genotype 1 receiving elbasvir/grazoprevir. Methods M2BPGi were serially measured at baseline, during and after therapy. Its diagnostic performance at baseline and sustained virological response at 24 weeks after treatment (SVR24) were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
3
4
0
Order By: Relevance
“…In addition, M2BPGi levels are correlated with other markers of liver fibrosis and ultrasound. This is consistent with the results of previous studies in Vietnam 18 , Thailand 19 , Japan 20 , and Egypt 21 . However, these studies used surrogate markers of liver fibrosis instead of liver biopsy, which is the gold standard.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, M2BPGi levels are correlated with other markers of liver fibrosis and ultrasound. This is consistent with the results of previous studies in Vietnam 18 , Thailand 19 , Japan 20 , and Egypt 21 . However, these studies used surrogate markers of liver fibrosis instead of liver biopsy, which is the gold standard.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, studies found that liver fibrosis regression occurs when DAAs are used for HCV treatment 14 , 19 , 21 and M2BPGi is a marker for patient survival after treatment with DAAs 17 . One paper even found that M2BPGi has a better performance than APRI in monitoring liver fibrosis 19 while another paper found that M2BPGi shows better performance than other markers in assessing liver fibrosis in HCV patients 22 . Most studies on M2BPGi levels and HCV were on patients treated with DAAs.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the published reports, we confirmed that serum M2BPGi level was highly correlated with LSM and hepatic fibrosis stage as determined with TE in our large-scale study [ 19 , 20 , 22 , 23 , 24 , 25 ]. However, the AUROCs of serum M2BPGi level in predicting patients with fibrosis stages of ≥F2, ≥F3, and F4 varied significantly among various studies.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to laying down ECM to promote hepatic fibrosis, these activated HSCs also secret M2BPGi, which serves as the juxtacrine-acting messenger to Kupffer cells during hepatic fibrogenesis [ 20 ]. Because there is a strong link between serum M2BPGi and hepatic fibrogenesis, studies have shown that serum M2BPGi levels are associated with fibrosis stage, dynamic fibrosis evolution, antiviral responses, presence of esophagogastric varices, risk of HCC occurrence or recurrence, extrahepatic malignancy, and survival in patients with HCV infection [ 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation